Proceedings of the 17th International Conference on World Wide Web 2008
DOI: 10.1145/1367497.1367532
|View full text |Cite
|
Sign up to set email alerts
|

Learning transportation mode from raw gps data for geographic applications on the web

Abstract: Geographic information has spawned many novel Web applications where global positioning system (GPS) plays important roles in bridging the applications and end users. Learning knowledge from users' raw GPS data can provide rich context information for both geographic and mobile applications. However, so far, raw GPS data are still used directly without much understanding. In this paper, an approach based on supervised learning is proposed to automatically infer transportation mode from raw GPS data. The transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
408
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(414 citation statements)
references
References 14 publications
2
408
0
4
Order By: Relevance
“…Many authors have suggested different extraction methods [8,18,20,39,38,40] based on clustering algorithms. Ashbrook et al [8] have proposed a two-step method to infer the significant locations.…”
Section: Related Workmentioning
confidence: 99%
“…Many authors have suggested different extraction methods [8,18,20,39,38,40] based on clustering algorithms. Ashbrook et al [8] have proposed a two-step method to infer the significant locations.…”
Section: Related Workmentioning
confidence: 99%
“…Giannotti et al [13] propose sequential pattern mining algorithms for mining trajectories of moving objects. Frequently occurring sequential patterns have been analyzed in [9,10,14,15]. However, the short and frequent movements of users identify more important behaviors.…”
Section: Modeling User Behaviormentioning
confidence: 99%
“…Another case is the project GeoLife proposed by Zheng Yu et al [3] from Microsoft Research Asia. The team conducted experiments using GPS data collected from 181 volunteers during a period of 2 years in the real world to mine valuable knowledge like individual life pattern [4] , transportation mode [5] and user similarity [6] , etc. Moreover, these GPS data are all shared freely on the Web.…”
Section: Introductionmentioning
confidence: 99%